﻿Synthesis, molecular docking, ADMET study and in vitro pharmacological research of 7-(2-chlorophenyl)-4-(4-methylthiazol-5-yl)-4,6,7,8-tetrahydroquinoline-2,5(1H,3H)-dione as a promising non-opioid analgesic drug - Aleksey D. Kravchenko; Natalia V. Pyatigorskaya; Galina E. Brkich; Larysa V. Yevsieieva; Alexander V. Kyrychenko; Sergiy M. Kovalenko (Belgorod National Research University, 2022)
Introduction: The discovery of novel drugs that can block the transmission of pain signals for treating the pain of various etiologies is an urgent topic in pharmaceutics. The aim of this paper is to synthesize and to investigate in vitro and in silico characteristics of a promising novel compound: 7-(2-chlorophenyl)-4-(4-methylthiazol-5-yl)-4,6,7,8-tetrahydroquinoline-2,5(1H,3H)-dione (HSV-DKH-0450). Materials and methods: The specific activity and the inhibitory mechanism of HSV-DKH-0450 were studied using the HEK293 culture cells expressing the IPTG-induced TRPA1 ion channels. Cardiotoxicity was determined by estimating the binding of HSV-DKH-0450 to the hERG channel. Inhibition of human liver cytochromes was determined by the effect on the activity of cytochromes 1A2, 2C9, 2D6, 2C8, and 3A4. Cellular toxicity was assessed by the effect on the viability of human hepatocytes. ADMET properties were evaluated using admetSAR and SwissADME web-based tools. Molecular docking was carried out using AutoDock Vina tools to predict the binding affinity of all HSV-DKH-0450 stereoisomers toward the TRPA1 and TRPV1 receptors. Results and discussion: In silico predictions of ADMET properties of HSV-DKH-0450 showed that it has optimal pharmaceutical profiles. A series of in vitro pharmacological studies revealed that HSV-DKH-0450 is a promising antagonist of the TRPA1 ion channel with the IC50 of 91.3 nM. The molecular docking of HSV-DKH-0450 stereoisomers against the TRPA1 and TRPV1 receptors demonstrates that they all are characterized by an approximately similar high binding affinity. Conclusion: The obtained data for substance HSV-DKH-0450 look promising for its further development as a potential therapeutic agent for pain relief. Graphical abstract: